The opinion of young people in megacities about environmental management and green consumption - Maria, Baynova; Alexander, Petrov; Olga, Gorkovaya; Maksim, Kuzminov; Victoria, Malikova (The journal of contemporary issues in business and government, 2021)
The article discusses the features of the formation of environmental awareness of educated youth and their active life position regarding constructive participation in the implementation of the sustainable development strategy of our country. Particular attention is paid to the study of the possibilities of developing the ecological culture of Russian educated youth as the most active and receptive to environmental values. The theoretical basis of the research was composed by the work of environmentalism researchers. The empirical base of the study was the results of a questionnaire survey of representatives of educated youth in Moscow and St.-Petersburg. The focus of the study is a system of norms, values, patterns of behavior that set the vector for the development of environmental awareness of educated young people in the existing socio-economic and political conditions. Particular attention is paid to the practices of young people, environmental activities, consumption reduction, information sources and assessment of measures to solve environmental problems. Separate waste collection and avoidance of environmentally hazardous products lead among activities, but do not cover the majority of respondents. The results of the study showed that a stable social group has emerged, among the educated youth of both capitals over the past decade, in which values and patterns have been formed, in which ecological consciousness is already quite clearly manifested. For representatives of this social group, the most acceptable actions are environmental volunteering, introduction to the practices of "green" consumption, separate collection of waste, social support for ethical business, an active political position on the effectiveness of measures of state environmental regulation. All this becomes the basis for the formation and sustainable reproduction of the structure of the ecological culture of educated youth. The results of the issue can be used in government policy in the ecology and government and local waste programs.